Профессиональная поддержка как способ повышения компетентности учителя - Онищенко, Е.А. (My University, 2016)
In the article possible ways of professional support to the certified teachers on the basis of the pedagogical difficulties revealed during supervision of practice are considered. The attention is focused on importance of modern teachers' methodological skills development.
Keywords: thecertifiedteacher; thereflectingpractician; competence; professionalsupport; methodologicalskills